2016
DOI: 10.1016/j.bios.2015.09.032
|View full text |Cite|
|
Sign up to set email alerts
|

A virus-based nanoplasmonic structure as a surface-enhanced Raman biosensor

Abstract: Fabrication of nanoscale structures with localized surface plasmons allows for substantial increase in sensitivity of chem/bio sensors. The main challenge for realizing complex nanoplasmonic structures in solution is the high level of precision required at the nanoscale to position metal nanoparticles in 3D. In this study, we report a virus-like particle (VLP) for building a 3D plasmonic nanostructure in solution in which gold nanoparticles are precisely positioned on the VLP by directed self-assembly techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…More recently, these applications have turned to using eVLPs rather than the infectious virus (Lebedev et al, 2016; Sainsbury et al, 2011, 2014; Wen et al, 2012). Therefore, it is of importance to structurally characterize eVLPs and analyze any significant differences that occur between the wild-type virus and eVLPs of CPMV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, these applications have turned to using eVLPs rather than the infectious virus (Lebedev et al, 2016; Sainsbury et al, 2011, 2014; Wen et al, 2012). Therefore, it is of importance to structurally characterize eVLPs and analyze any significant differences that occur between the wild-type virus and eVLPs of CPMV.…”
Section: Discussionmentioning
confidence: 99%
“…These can be generated by co-expression of the CP precursor VP60 along with the 24K viral proteinase in Nicotiana benthamiana (Montague et al, 2011; Saunders et al, 2009). CPMV eVLPs generated this way have already proven useful as reagents for bio- and nanotechnology applications (Lebedev et al, 2016; Sainsbury et al, 2011, 2014; Wen et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The sensing scheme of SERS benefits from the enhancement of Raman scattering by providing the modulation of surface plasmon polaritons at a greater distance from the metallic nanoparticle surface, thereby offering higher sensitivity than that of SPR and LSPR. Lebedev et al reported a SERS platform applied to the detection of viral DNA using nanoclusters (NC) of gold nanoparticles [ 44 ]. SERS experiments were performed on lone gold nanoparticles, individual nanoclusters, and in two distinct plasmonic nanoclusters.…”
Section: Biosensing Strategiesmentioning
confidence: 99%
“…The genome of CPMV is bipartite, with RNA-2 being the principal component of expression vector development. CPMV has been utilized extensively in antigenic presentation and full-length protein expression as part of a fusion protein that can undergo proteolytic cleavage to release the therapeutic protein, as well as in material science research, such as the formation of magnetic clusters and biosensors [ 63 , 64 , 65 , 66 ]. For example, Medicago, Inc. (Durham, NC, USA) has used the CPMV vector to generate virus-like particles (VLPs) carrying influenza virus HA antigens [ 67 ].…”
Section: Virus Expression Vectors Based On Comovirusesmentioning
confidence: 99%